Implication of pharmacists in Cluj County in managing the COVID-19 pandemic - Elena Dinte; Teodora Zehan; George Florin Miclaus; Niculina Ileana Sandor; Daniela Vaida; Simona Vostinaru (Amaltea Medical Publishing House, 2020)
Objectives. To highlight the involvement of pharmacists working in community pharmacies in the management of the COVID-19 pandemic, to identify the main services provided by pharmacists in order to sustain pharmaceutical care and the main actions taken to minimize the encountered difficulties during the March 16th 2020 - September 15th 2020 timeframe. Material and methods. A questionnaire was elaborated and then distributed to community pharmacies in Cluj County. Based on the results obtained after the completion of the questionnaire, an evaluation of the following factors could be made: pharmacy opening hours, staff plan and the shortage of supplies and personal protective equipment against the Coronavirus disease. Results. The activity in a total of 246 community pharmacies (80.92% of the total number of community pharmacies in Cluj County) was analyzed, of which 134 community pharmacies (54.47% of the number of analyzed ones) adjusted their opening hours, most frequently dependent on the requirements and conditions generated by the state of emergency (in 73.88% of the number of analyzed cases), some of which chose to adjust the staff plan as well. The most important matter that affected the activity of pharmacists during the pandemic was the shortage of personal protective equipment (such as face masks and gloves), as well as the shortage of pharmaceutical grade ethanol, intended for the preparation of antiseptic and disinfectant solutions (sanitizers). Conclusions. The pharmacists have shown an active involvement in maintaining the pharmaceutical service and the public health of the population during the COVID-19 pandemic as a part of the frontline healthcare professionals. They were able to elaborate new strategies adapted to the requirements generated by the community and to the restrictions generated by the state of emergency in order to fulfil their duty. During this period of time, the importance of preparation activity in pharmacy was strongly emphasized, the most frequent problem encountered being the difficult supply with personal protective materials.